2016
DOI: 10.3329/bjms.v15i2.28794
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of ST-segment resolution influencing in hospital outcome after primary percutaneous coronary intervention and fibrinolysis (with streptokinase) in patients with acute ST-segment elevation myocardial infarction

Abstract: Abstract:Background: Coronary artery disease (CAD) is the most common cause of mortality & morbidity in all over the world. Reperfusion therapy is the cornerstone for treating acute STsegment elevation myocardial infarction. Effective reperfusion in STEMI can be achieved by either fibrinolysis or primary percutaneous coronary intervention (PPCI). PPCI generally produces better outcomes than fibrinolysis but is not widely available. ST-segment abnormalities play a fundamental role in assessment and decision mak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
1
1
0
Order By: Relevance
“…This study showed that the 90‐minute ST resolution was significantly higher in PPCI group ( P = 0.04), and this is in agreement with Rahman et al who reported that ST‐segment resolutions were significantly more in PPCI than thrombolysis at 90 minutes (73.15 ± 18.76 vs 60.06 ± 23.33%, P < 0.015).…”
Section: Discussionsupporting
confidence: 91%
“…This study showed that the 90‐minute ST resolution was significantly higher in PPCI group ( P = 0.04), and this is in agreement with Rahman et al who reported that ST‐segment resolutions were significantly more in PPCI than thrombolysis at 90 minutes (73.15 ± 18.76 vs 60.06 ± 23.33%, P < 0.015).…”
Section: Discussionsupporting
confidence: 91%
“…Clinical methods used for excluding the diagnosis of coronary artery illness include risk factor assessment, electrocardiography (ECG), cardiac biomarker assessment, cardiac nuclear imaging, echocardiography, cardiac magnetic resonance imaging and invasive coronary angiography. These methods have drawbacks, such as invasiveness, radiation injury, resource allocation and low specificity, and impose a heavy economic burden on sufferers [5,6]. Recently, speckle tracking echocardiography (STE) has been used to evaluate coronary stenosis through the frame-by-frame tracking of the speckle echo motion trajectory of myocardial synchronous movement in the region of interest; it can obtain multiple parameters that reflect myocardial mechanical changes in the longitudinal, radial, circumferential and rotational directions, thus enabling evaluating the local and overall mechanical properties of the myocardium [7,8].…”
Section: Introductionmentioning
confidence: 99%